First prospective multicenter experience with the 7 French Glidesheath slender for complex transradial coronary interventions. Issue 6 (27th August 2016) - Aminian, Adel; Iglesias, Juan F.; Van Mieghem, Carlos; Zuffi, Andrea; Ferrara, Angela; Manih, Roukos; Dolatabadi, Dariouch; Lalmand, Jacques; Saito, Shigeru
Abstract : Purpose: To assess the feasibility and safety of the 7 French (Fr) Glidesheath Slender for complex transradial (TR) percutaneous coronary interventions (PCI). Background: The TR approach is increasingly used worldwide for coronary and peripheral vascular interventions. However, the small size of the radial artery remains an important limitation for the use of large‐bore guiding catheters (>6 Fr), restricting thereby the treatment of highly complex lesions through the TR approach. The 7 Fr Glidesheath slender (Terumo, Tokyo, Japan) is a new dedicated radial sheath with a thinner wall and hydrophilic coating. It combines an inner diameter compatible with any 7 Fr guiding catheter and an outer diameter smaller than current 7 Fr sheaths. Methods: Prospective multicenter registry of complex TR PCI cases using the 7 Fr Glidesheath Slender to determine the procedural success, rates of vascular complications, radial spasm, and radial artery occlusion (RAO). Results: A total of 60 patients were included. Procedural success was 97% with only one access‐site crossover. The use of a 7 Fr guiding catheter was indicated for the treatment of highly complex coronary lesions including distal left main (LM) disease ( n = 20), complex non‐LM bifurcation lesions ( n = 16), chronic total occlusion ( n = 15), and severely calcified vessels requiring rotational atherectomy ( n = 10). There were three vascular access‐site complications (4.7%) including two moderate (type II) local hematoma and one uncomplicated guiding catheter‐induced brachial artery dissection. None of the patients experienced major bleeding. The occurrence of radial spasm was reported in seven patients (11%). Doppler ultrasound imaging of the radial artery at 1 month was available in 62 of 64 radial access with three cases of RAO (4.8%). Conclusions: Use of the 7 Fr Glidesheath slender for complex coronary interventions is feasible and associated with a high rate of procedural success and a low rate of vascular complications. These favorable results need be confirmed in larger multicenter studies. © 2016 Wiley Periodicals, Inc.